Implications of the food crisis for long-term agricultural development - Minot, Nicholas (International Food Policy Research Institute, 2008)
The prices of maize, wheat, rice, and other crops have more than doubled over the past two years. These price hikes have been catalyzed by various factors including the rising cost of oil, biofuel subsidies in the US and Europe, the depreciation of the US dollar, the prolonged drought in Australia, and restrictions on the export of rice and wheat by various countries including Vietnam, India, Russia and Argentina. However, these short-term "headline" causes would not have had the same dramatic effect on world markets if we had not experienced a 5-10 year period of disequilibrium, in which the growth in cereal demand outpaced the growth in cereal production. This imbalance has been reflected in declining global cereal stocks since 2000. Cereal demand has been growing at 2-3% per year, thanks to rising incomes in China, India, and, more recently, sub-Saharan Africa. As incomes rise, people diversify their diet and consume more meat and other animal products, increasing the demand for feed, particularly maize. Meanwhile, yield growth in these cereals has declined from 3% in the 1970s to 1-2% in the 1990s, largely due to declining public investment in agricultural research.